2014
DOI: 10.7314/apjcp.2014.15.1.257
|View full text |Cite
|
Sign up to set email alerts
|

Association of +405C>G and +936C>T Polymorphisms of the Vascular Endothelial Growth Factor Gene with Sporadic Breast Cancer in North Indians

Abstract: Background: Vascular endothelial growth factor (VEGF), an endothelial cell specific mitogen, has been implicated as a critical factor influencing tumor related angiogenesis. The aim of present study was to evaluate the relationship between VEGF +936C>T and +405C>G polymorphisms of VEGF with risk of breast cancer in Punjab, India. Materials and Methods: We screened DNA samples of 192 sporadic breast cancer patients and 192 unrelated healthy, gender and age matched control individuals for VEGF +936C>T and +405C>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…NCOA1 promotes angiogenesis in breast tumors by enhancing the transcription of VEGFa via HIFα and AP-1 [95]. Previous studies from our lab on breast cancer patients from same region have reported association of VEGF polymorphisms +405C>G, +936C>T, -2549 Insertion/Deletion, −152G/A, −116G/A, −165C/T and −141A/C with breast cancer risk but no association of VEGF -417C/T, -172C/A and -160C/T and HIF1α polymorphisms (g.C111A, g.C1772T and g.G1790A) with breast cancer risk [96][97][98][99].…”
Section: Discussionmentioning
confidence: 95%
“…NCOA1 promotes angiogenesis in breast tumors by enhancing the transcription of VEGFa via HIFα and AP-1 [95]. Previous studies from our lab on breast cancer patients from same region have reported association of VEGF polymorphisms +405C>G, +936C>T, -2549 Insertion/Deletion, −152G/A, −116G/A, −165C/T and −141A/C with breast cancer risk but no association of VEGF -417C/T, -172C/A and -160C/T and HIF1α polymorphisms (g.C111A, g.C1772T and g.G1790A) with breast cancer risk [96][97][98][99].…”
Section: Discussionmentioning
confidence: 95%
“…VEGF expression can play a role in regulating angiogenesis is involved in promoting endothelial cell proliferation and regulating the extracellular matrix in the blood vessels (Roy et al, 2006;Kushner and Bautch, 2013). Several functional SNPs in the VEGF gene can alter the expression levels of VEGF protein in cancer cells, thus influencing the tumor angiogenic activity and accelerating carcinogenesis such as bladder cancer, breast cancer, lung cancer, colorectal cancer, prostate cancer, ovarian cancer, and osteosarcoma (Li et al, 2010;Jaiswal et al, 2013;Kapahi et al, 2014;Deng et al, 2014;Lau et al, 2014;Chen et al, 2014;Wang et al, 2014). Jaiswal et al (2013) reported that VEGF polymorphisms may play a significant role in mediating bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Jaiswal et al (2013) reported that VEGF polymorphisms may play a significant role in mediating bladder cancer. Kapahi et al (2014) examined an Indian population and found that the VEGF +936C>T and +405C>G polymorphisms were associated with an increased risk of breast cancer. Lau et al (2014) conducted a study in a Malaysian population and found that the VEGF gene polymorphism has a role in the development of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF is a potent regulator of angiogenesis and thus plays a role in the development and prognosis of solid tumors (Kapahi et al, 2014;James et al, 2014). Several common single-nucleotide polymorphisms (SNPs) in the VEGF gene have been reported to have a role in gene expression.…”
Section: Introductionmentioning
confidence: 99%